Cardiopulmonary arrest and in-hospital outcomes in young patients with acute myocardial infarction: insights from the Japanese nationwide registry. (3rd October 2022) - Ando, H; Yamaji, K; Kohsaka, S; Ishii, H; Sakakura, K; Goto, R; Nakano, Y; Takashima, H; Ikari, Y; Amano, T
Abstract: Background: Cardiopulmonary arrest (CPA) is the most serious presentation of acute myocardial infarction (AMI). However, the frequency and prognostic impact of CPA in young patients with AMI have been still unclear. Objectives: This study aimed to characterize AMI in young patients who underwent primary percutaneous coronary intervention using large-scale nationwide all-comer registry data in Japan (J-PCI registry). Methods: Data on risk factor profiles, clinical features, post-procedural complications, and in-hospital outcomes were reviewed within the J-PCI registry between 2014 and 2018. Results: Among 213, 297 patients with AMI, 23, 985 (11.2%) were young (age, 20–49 years). Compared with the older group (age, 50–79 years; n=189, 312), the young group included a higher number of men, smokers, patients with dyslipidemia, and patients with single-vessel disease, and a lower number of patients with hypertension and diabetes. Despite favorable clinical profiles, younger age was associated with a higher rate of presentation with CPA (Figure 1). Further, concomitant CPA was strongly associated with in-hospital mortality in the young group (Table 1). Conclusions: Young patients with AMI presented a higher risk of CPA than older patients, which was strongly associated with in-hospital mortality. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): JSPS KAKENHI